Strategic plan for Patahian - Bilao, Jennifer M.; Ellson, Adela G.; Pabularcon, Liza N. (Davao City School of Management, University of the Philippines Mindanao, 2007)
This paper is focused in the formulation of a strategic for Patahian, a couturier shop established in 1995 by partners Aztec Barba and Dodjie Batu, who raised the business from humble beginnings to a recognized fashion and tailoring house in General Santos and Davao City. Patahian has successfully expanded its operations to two locations within five years. With the sprouting of businesses of the same nature, Patahian wanted to formulate a strategic plan that will provide a blueprint from 2007 to 2012. This strategic plan is a result of an in-depth analysis of its internal and external environment and an evaluation of its corporate objectives. The first chapter provides the backgrounder, industry information, the objectives for conducting the study, significance of the study, and most importantly the strategic framework being used for the company. Chapter 2 presents information about the subject company, Patahian and its original corporate vision, mission, and goals. Chapter 3 discusses the internal audit being done for the subject company. Specifically it tackles the general management, marketing, and operations. With this, the strengths identified are: (1) size of organization is small and manageable; (2) competitive corporate uniform and luxe gown designs; (3) strategic location of shops; (4) built a prestige name for luxe gowns designs; (5) selects and uses best and quality materials; (6) major turnaround in finances from a net loss of 7% in 2003 to a 4% increase in income in 2004 and 6% in 2005; and lastly (7) loyal and friendly staff. The weaknesses noted are (1) record-keeping is manually maintained; (2) tendencies of delay in delivery; (3) workforce is minimal and especially felt during big volume orders; (4) their craft only concentrate on women?s clothing. Following is the external audit which discusses the economic, social, cultural, competitive, and industrial issues bordering the subject company that helped identify the opportunities and threats. The opportunities are promising as (1) increasing popularity of corporate uniforms among corporate offices in the region; (2) increase demand in ready-to-wear clothing; (3) limited stores with RTW formal clothing in the region; (3) presence of customers who were frustrated with pioneer elite dressmakers; (4) increasing awareness of men into fashionable and luxe clothes. The threats observed were (1) rise of other couturier shops in the city; (2) demand for walk-in couturier services still under-developed; (3) price sensitivity of local customers of luxe wear; (4) inflation rate increase; and (5) continued popularity of ready-to-wear designer clothing. The internal and external factor evaluation matrices in IFE and EFE revealed scores that hit the average. Thus, the company is considered to be in a strong internally and is able to respond practically to the existing opportunities and threats in the industry by capitalizing on external opportunities and avoiding threats. With the thorough exploration of the internal and external factors of the subject company, a proposal for an improved corporate vision, mission, and goals is prepared in Chapter 5. Add to that, corporate values were formulated to give Patahian standards of behavior to be followed by the people in the company as they work to achieve their vision, mission, and goals. Chapter 6 discusses the strategic proposals and shoes the use of SWOT (Strengths-Weaknesses-Opportunities-Threats) Matrix and the QSPM (Quantitative Strategic Planning Matrix) as its tools to come up with winning strategies for the subject company. As a result, the following strategies stirred up: (1) increase corporate accounts in the region; (2) create more competitive designs; (3) venture into creating ready-to-wear designs for local designers brands; (4) put up an outlet in a leading mall for more visibility; (5) with best designs, make the prices competitive; (6) with the increase in demand for expansion, there should be an increase in workforce; (7) venture into designing and producing men?s wear, (8) improve recordkeeping system as corporate accounts increase; and (9) outwit other couturier shops by being able to deliver on time. Among these strategies, the most attractive choice for Patahian as a result of the QSPM evaluation is putting up an outlet in a leading mall for more visibility. To achieve the strategic choice, Chapter 7 and 8 provide the implementing programs and controls. Step-by-step procedures for the areas of organization, operation, marketing, and finance are prepared to accomplish the decision. This strategy will be implemented in for the duration of five years. If properly implemented, this strategy is expected to enable Patahian to achieve higher revenue and make a bigger name in the corporate wears, luxe gowns, and casual designer clothing market.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, April 2007
Keywords: Strategic plan